Effectiveness of Distraction Techniques on Pain Intensity during Immunization among Infants (International Journal of Nursing Education, 2019)
Background: One of the most dramatic advances in pediatic nursing is the atraumatic care . Pain associated with some investigation, treatment or procedures is known as procedural pain. Distraction is non pharmacological method which is used for diverting attention from noxious stimulus by passively redirecting the attention or by actively performed by the subject in the performance of diversion technique. Material and method: A true experimental multiple intervention post test control design was used. There were100 infants selected using simple random sampling technique and were randomly allocated in various groups such as electronic toy group, key toy group, simple toy group and control group using lottery method. During immunization, distraction techniques were shown to experimental groups and routine care was given to control group. Research tool was submitted to 7 experts from various specialists for validity. Reliability was calculated by Kappa method and it was 0.83 of FLACC pain scale to assess pain intensity during immunization among infants. Data collection was done in January 2017. The obtained data was analyzed and interpreted in terms of objectives and research hypotheses. Analysis was done by using descriptive and inferential statistics. Results: The results revealed that mean pain score of control group was higher (7.16±0.16) as compared to that of electronic toy group (2.60± 0.16) , key toy group(4.80±0.22) and simple toy group (5.44±0.18) . The difference between mean pain score of infants in electronic toy group, key toy group, simple toy group with control group was found to be statistically significant at p
Keywords: Immunization, Pain, Distraction techniques, Multiple intervention post test design.